1978
DOI: 10.1016/s0022-5347(17)57247-x
|View full text |Cite
|
Sign up to set email alerts
|

Probable Endometrial Carcinoma of the Prostate, Crossed Renal Ectopia and Dermatomyositis in a 32-year-old Man

Abstract: An unusual type of prostatic carcinoma associated with crossed renal ectopia and dermatomyositis is reported in a young man. Infiltration by an epithelial tumor filled the enlarged prostate with soft papillary masses. Cystoprostatectomy and removal of a single large pelvic lymph node metastasis were done. Histologically, the tumor resembled endometrial carcinoma and may have arisen from paramesonephric tissue in the prostate. Large amounts of immunoglobulins were found in the tumor tissue. The patient has surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These authors described large numbers of plasma cells within the prostate tissue, and IgG staining within prostate tissue as well as skin biopsies. They could not detect circulating antibodies using techniques available at that time, but suggested that an autoimmune reaction might be involved in the disease process 16 . There has otherwise been no investigation, to our knowledge, prior to our report of an autoimmune association between dermatomyositis and prostate cancer.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…These authors described large numbers of plasma cells within the prostate tissue, and IgG staining within prostate tissue as well as skin biopsies. They could not detect circulating antibodies using techniques available at that time, but suggested that an autoimmune reaction might be involved in the disease process 16 . There has otherwise been no investigation, to our knowledge, prior to our report of an autoimmune association between dermatomyositis and prostate cancer.…”
Section: Discussionmentioning
confidence: 88%
“…Dermatomyositis has a strong association with malignancy; however, it has most commonly been associated with ovarian cancer and lung cancer 13,27 . To our knowledge, there have only been nine previous case reports of dermatomyositis being associated with prostate cancer 14–22 . Most of these reports describe an initial presentation of dermatomyositis followed by a diagnosis of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations